Adolescents' experiences of street harassment: creating a typology and assessing the emotional impact. Issue 1 (11th February 2019) - Betts, Lucy; Harding, Rachel; Peart, Sheine; Sjolin Knight, Catarina; Wright, David; Newbold, Kendall
Abstract : Purpose: Research examining young people's experiences of harassment has tended to focus on the school and digital environment. Despite street harassment being identified as a common experience for adult women, very few studies have explored adolescents' experiences of street harassment. The paper aims to discuss this issue. Design/methodology/approach: A person-centred analytical approach, based on experienced reporting, was used to create a typology of street harassment. The reports of street harassment were received from 118 (68 female, 43 male, no gender reported in 7) 11-15-year olds over a 6-8 week period. Findings: Cluster analysis revealed four distinct groups: "predominately verbal", "non-verbal/non-direct", "other incident", and "all forms". Young women and those in the "all forms" group reported experiencing greater negative emotions following the episode of street harassment. Young men were equally as likely as young women to report experiencing street harassment. Originality/value: The findings uniquely highlight that adolescents experience distinct types of street harassment, some of which are associated with negative emotions.